If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3w + 6 = 4w + 0 Reorder the terms: 6 + 3w = 4w + 0 Reorder the terms: 6 + 3w = 0 + 4w Remove the zero: 6 + 3w = 4w Solving 6 + 3w = 4w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-4w' to each side of the equation. 6 + 3w + -4w = 4w + -4w Combine like terms: 3w + -4w = -1w 6 + -1w = 4w + -4w Combine like terms: 4w + -4w = 0 6 + -1w = 0 Add '-6' to each side of the equation. 6 + -6 + -1w = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1w = 0 + -6 -1w = 0 + -6 Combine like terms: 0 + -6 = -6 -1w = -6 Divide each side by '-1'. w = 6 Simplifying w = 6
| 5=a+1 | | b/-3=-1 | | 3/4n=15/2 | | k+3/5=-3/20 | | 5/6t=5 | | k-3/5=-1/10 | | n-4=-25/6 | | b+9/10=13/20 | | -5/8+b=35/8 | | 6+m=20/3 | | 2sin^2x+5sinx+2=0 | | -5/7+d=79/7 | | m+2/3=-10/3 | | b-6=-2 | | m+3/4=-1/4 | | t+1=7/10 | | -1/2+w=-7/2 | | -1+k=-3/10 | | 2sinx^2+5sinx+2=0 | | 4n-6=10n+0 | | n+6=58/9 | | w+5/6=47/6 | | w+1=-8 | | b-8=-79/11 | | -4/5w=-16/25 | | w+1/6=17/18 | | 1/2b=11/2 | | t-2/9=-1/45 | | w+1/2=-19/2 | | t/4=5 | | m+2=-8 | | -19/3=b+2/3 |